'Tapanduka Zvamuchese': Facebook, 'unruly publics', and Zimbabwean politics. Issue 1 (2nd January 2019) - Karekwaivanane, George Hamandishe
ABSTRACT: This paper examines the role that a Facebook account operating under the name Baba Jukwa played in the run up to the Zimbabwean 2013 election. It argues that Baba Jukwa was able to convoke an 'unruly public' that was situated in opposition to the state-controlled public sphere, and one that was transnational in its reach. Through a close examination of the posts by Baba Jukwa and the debates they generated, it uncovers the key features of this public, namely, the use of symbolically laden pseudonyms, the emergence of a vernacular discourse that was articulated in multiple registers, and the prevalence of conspiracy theorizing. The paper also highlights the way that these publics are inflected by older socio-cultural and political practices, and the efforts of participants in the public to creatively fused the past and the present.